2015
DOI: 10.1111/anu.12348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary yellow loess as an antibiotic replacer on growth, immune responses, serological characteristics and disease resistance in rainbow trout,Oncorhynchus mykiss

Abstract: A 12 weeks of feeding trial was conducted to evaluate the effects of different levels of dietary yellow loess as an antibiotic (oxytetracycline) replacer in rainbow trout, Oncorhynchus mykiss. Five experimental diets were formulated to contain no antibiotics or yellow loess (control/CON), three graded levels of yellow loess 5 (YL 5 ), 10 (YL 10 ) and 20 g YL kg À1 diet (YL 20 ) and oxytetracycline at 5 g OTC kg À1 diet. Forty-five fish averaging 39.4 AE 1.6 g (mean AE SD) were randomly distributed in to 15 aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…On the other hand, SOD are metalloenzymes that catalyze the dismutation of the superoxide radical (O 2-) into hydrogen peroxide (H 2 O 2 ) and molecular oxygen (O 2 ) (Shao et al 2010), which provides an important defense against oxidative damage. In line with the present study, improved immune responses have been recorded in cultured fish with several feed additives such as the combination of b-glucan and BAISM (Yoo et al 2007), b-glucan (Ai et al 2007), herbal extracts (Chelladurai et al 2014), yellow loess (Lee et al 2015b), Song-gang Ò stone (Lee et al 2015b) and Yucca meal (Njagi et al 2017). …”
Section: Innate Immune Responsessupporting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, SOD are metalloenzymes that catalyze the dismutation of the superoxide radical (O 2-) into hydrogen peroxide (H 2 O 2 ) and molecular oxygen (O 2 ) (Shao et al 2010), which provides an important defense against oxidative damage. In line with the present study, improved immune responses have been recorded in cultured fish with several feed additives such as the combination of b-glucan and BAISM (Yoo et al 2007), b-glucan (Ai et al 2007), herbal extracts (Chelladurai et al 2014), yellow loess (Lee et al 2015b), Song-gang Ò stone (Lee et al 2015b) and Yucca meal (Njagi et al 2017). …”
Section: Innate Immune Responsessupporting
confidence: 88%
“…Moreover, fish fed the YM, BG and CONT diets did not show significant differences in terms of FE and PER. The observations with the SG diet is comparable to the findings by Lee et al (2015b) and Won et al (2017) with Song-gang Ò stone and yellow loess, respectively, in rainbow trout Oncorhynchus mykiss as well as Shahkar et al (2015) with Macsumsuk Ò in Nile tilapia Oreochromis niloticus. Growth and feed efficiency improved in olive flounder Paralichthys olivaceus fed a combination of b-glucan and BAISM-contained diets (Yoo et al 2007).…”
Section: Growthsupporting
confidence: 84%
See 2 more Smart Citations
“…(), lysozyme activity in fish has been shown to be modulated by dietary HUFA levels. One of the other antioxidant enzymes, SOD, plays a role in removing reactive oxygen species from the cellular environment by catalysing the dismutation of two superoxide radicals to hydrogen peroxide and oxygen (Fattman, Schaefer, & Oury, ; Lee et al., ; Lin, Shie, & Shiau, ; Shao et al., ). In this study, similar trend with the performance of lysozyme was also observed in SOD activity indicating the improvement of fish immune system by dietary EPA.…”
Section: Discussionmentioning
confidence: 99%